Mast cell number, substance P and vasoactive intestinal peptide in irritable bowel syndrome with diarrhea. (January 2013) - Sohn, Won; Lee, Oh Young; Lee, Sang Pyo; Lee, Kang Nyeong; Jun, Dae Won; Lee, Hang Lak; Yoon, Byung Chul; Choi, Ho Soon; Sim, Jongmin; Jang, Ki-Seok
Abstract Background. Recent studies have shown that mast cells play an important role in irritable bowel syndrome (IBS). We investigated the relationship between mast cells and the gut hormones substance P and vasoactive intestinal peptide (VIP) in irritable bowel syndrome with diarrhea (IBS-D). Methods. Colonoscopic biopsies were performed on the rectal mucosa of 43 subjects (IBS-D patients: 22, healthy volunteers: 21) diagnosed according to the Rome III criteria. Mast cells, and substance P & VIP were evaluated by quantitative immunohistology and image analysis. Mast cells were counted as tryptase-positive cells in the lamina propria, and substance P and VIP levels were expressed as percentages of total areas of staining. Results. Mast cell counts were higher in IBS-D patients than healthy volunteers (9.6 ± 3.3 vs. 5.7 ± 2.5/high power field (HPF), p < 0.01). Substance P was also elevated (0.11 ± 0.08% vs. 0.03 ± 0.02 %, p < 0.01) while VIP was only high in women with IBS-D. Mast cell counts were positively correlated with levels of substance P & VIP in women but not men (women: r = 0.625, p < 0.01 for substance P and r = 0.651, p < 0.01 for VIP). However, mast cell counts were not correlated with IBS symptoms including abdominal pain. Conclusion. Mast cells are activated leading to the raised levels of substance P & VIP in IBS-D patients. However, the correlation between mast cells and levels of substance P & VIP differs according to gender.